Quantitative Analysis of Nebulized Inhalation Therapy for Neonatal Respiratory Distress Syndrome - LIU Weihua; XIE Qian; ZHOU Yaling (Journal of Harbin University of Science and Technology)
To treat neonatal respiratory distress syndrome ( NRDS) is to deliver pulmonary surfactant ( PS) to lungs with either invasive or non-invasive methods. This paper ，based on the pharmacokinetic principles and administration ways ，established a mathematical model of nebulized inhalation of PS for the treatment of NRDS，which was non-invasive for the newborn，to quantitatively analyze the fluctuation of blood oxygen partial pressure ( PaO2 ) after medication. For the regimen of the newborn ’s nebulized inhalation of PS ，after simulating the variation of PaO2 with data limited within a normal range ，this paper found that nebulized inhalation was similarly effective as endotracheal intubation ，and that the former prevailed for its non-invasiveness. It could also simulate the changing trend of PaO2 after personal PS medication of NRDS，which has thus provided a theoretical backup for the clinical application of atomization inhalation technology.